Adoção de produtos e serviços tecnológicos pelo consumidor : uma avaliação da aplicabilidade da technology adoption propensity no contexto brasileiro - Bittencourt, Rafael (2016)
The constant evolution of technology as well with its increasing influence on our daily lives has directly affected the way we live, and consequently the way we consume. This increasing importance of technology has attracted the interest from researchers in the marketing area. This process has contributed to a significant increase in the number of studies that seek a better understanding of the consumer’s relationship with technology and its adoption process. That said, the technology propensity adoption emerges as an important construct to understand this complex consumer's relationship with technology. In this sense, the scale Technology Propensity Adoption (TAP) developed by Ratchford and Barnhart (2011) suggest a model comprising inhibiting factors (dependence and vulnerability) and factors that encourage (optimism and proficiency) the adoption of technology represents an important advance in understanding this relationship. Thus, the main objective of this research is to verify the applicability of TAP scale in the Brazilian context, by replicating the measuring instrument to a sample of 428 consumers in the city of Porto Alegre. The results show the validity of TAP scale as a reliable and valid instrument for measuring the technology adoption propensity of the brazilian consumers, confirming the four dimensions proposed by the original study. The data also indicate significant differences betwen consumers in this study compared to the original study of Ratchford and Barnhart (2011), in which the consumers of the present study are more likely to adopt technologies. It is also possible to observe a significant difference between the different consumer profiles surveyed, with more or less technological experience, regarding to the proficiency construct in the process of adoption of the technology. The final considerations discuss the academic and managerial implications of these findings.